AN OVERVIEW OF MICRO, SMALL AND MEDIUM ENTERPRISES (MSMES) IN THE STATE OF UTTAR PRADESH - Midhat Fatima; Prof. S. M. Jawed Akhtar (EPRA International Journal of Economic and Business Review(JEBR), 2023)
Micro, Small and Medium enterprise sector holds immense importance for the Indian Economy. It plays a very crucial role in providing employment, generating output and contributing to exports of the country. MSMEs are widely distributed across the different states of the country. The state of Uttar Pradesh holds the highest number of MSMEs. Its large labour population and developed infrastructure provide it great potential for the expansion and improvement of the micro, small, and medium enterprise sector. This study has examined the performance of the MSME sector in UP using secondary data gathered from the website of the Ministry of MSME, Government of India. The examination of four MSME censuses in UP has shed insight into the success of the state’s small and medium-sized business sectors. Recent trends in the micro, small, and medium-sized enterprise (MSME) sector were analysed by looking at the Udyog Aadhaar Memorandum and Udyog registrations. The CAGR has been computed in Microsoft Excel for the purpose of examination. The state of Uttar Pradesh’s (UP) various initiatives and policies are reviewed to determine the state’s contribution to the growth and improvement of the industry. There has been an increase in the number of msme units, as well as employment, investment, and output, over all four MSME censuses, with the most recent two censuses showing the most dramatic increase. The MSME units in UP have increased at a compound annual growth rate (CAGR) of 0.45 per cent after the implementation of the Udyog Aadhaar Memorandum (2015-16). In order to meet the unique challenges faced by the MSME sector, the UP government has developed a series of policies that are crucial to the success of the sector.